1995
DOI: 10.1016/s0886-3350(13)80146-0
|View full text |Cite
|
Sign up to set email alerts
|

Posterior capsule reopacification after neodymium:YAG laser capsulotomy

Abstract: We report a case of complete posterior capsule reopacification after successful neodymium:YAG (Nd:YAG) capsulotomy in an adult. Review of the records of all patients who had an Nd:YAG capsulotomy at our hospital revealed an incidence of reopacification of 0.7%. All affected patients were younger than 50 years at the time of cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Using the capsular bag model (Liu et al, 1996), we compared cell proliferation in PCO specimens incubated in culture media with human lenses and capsular bags previously described . Reproliferation after YAG laser capsulotomy is described (McPherson and Govan, 1995) and has been reported, particularly in diabetic eyes with severe proliferative retinopathy (Jones, McLeod and Boulton, 1995). We tested, therefore, the possibility that high serum concentration, long incubation period and/or ®bres/IOL removal could, in vitro, reproduce the pattern of reproliferation observed in selected patients in vivo after YAG laser treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Using the capsular bag model (Liu et al, 1996), we compared cell proliferation in PCO specimens incubated in culture media with human lenses and capsular bags previously described . Reproliferation after YAG laser capsulotomy is described (McPherson and Govan, 1995) and has been reported, particularly in diabetic eyes with severe proliferative retinopathy (Jones, McLeod and Boulton, 1995). We tested, therefore, the possibility that high serum concentration, long incubation period and/or ®bres/IOL removal could, in vitro, reproduce the pattern of reproliferation observed in selected patients in vivo after YAG laser treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] To our knowledge, this is the first case of histologically proven lens capsule proliferation mimicking epithelial ingrowth. Epithelial ingrowth is a rare, devastating condition in which conjunctival or corneal epithelial cells migrate through the wound and proliferate, resulting in IOP elevation due to trabecular blockage by mucus and epithelial cells.…”
Section: Discussionmentioning
confidence: 69%
“…The disadvantage of a smaller PCCC is the visual axis obscuration caused by the proliferation of the lens epithelial cells from the PCCC margin. [22][23][24][25] The reported incidence of visual axis obscuration with PMMA IOLs is 60% to 100% when capsulotomy is not combined with anterior vitrectomy. 26 In our study, we reported that in children younger than 5 years who underwent PCCC without anterior vitrectomy using PMMA IOLs, 62.5% developed visual axis obscuration at an average follow-up of 13.3 months.…”
Section: Discussionmentioning
confidence: 99%